Characterization of candidate receptor proteins that bind dengue viruses using proteomics - Jong, Wan Wui. (Universiti Malaysia Sarawak (UNIMAS), 2006)
The identification and characterization of cell surface receptor(s) and other interacting cellular proteins of dengue virus (DENV) have not been successful since multiple approaches taken in various studies produced different results that are too complicated for comparison.